RESPON PESANTREN TERHADAP PENERAPAN PROTOKOL KESEHATAN DI TENGAH PANDEMI COVID-19 (STUDI KASUS TERHADAP TIGA PESANTREN DI SUMATRA SELATAN) - Nugroho Nugroho; Zaki Faddad Syarif Zain; Arpah Nurhayat (LP2M IAIN Palangka Raya, 2021)
This study was to reveal the theological response and application of health protocols in Islamic boarding schools during the COVID19 pandemic. The data were obtained through observations, observations and interviews in three Islamic boarding schools: Ittifaqiyah, Aulia Cendikia and Al Burhan, a Salaf Islamic Boarding School. Aulia Cendikia is affiliated with NU and Al Burhan with Jamaah Tabligh, while Ittifaqiyah is the largest pesantren in the province but is not affiliated with any religious movement. This study revealed that in the application of health protocols in Islamic boarding schools during the pandemic, there were two things. First, Islamic boarding schools applied rules in the form of SOPs for virus prevention strictly. This was performed by Pesantren Aulia Cendikia and Ittifaqiyah. Meanwhile, Al Burhan tent to apply loosely. It was concluded that the level of an Islamic boarding school and the school it adhered could determine the response to health protocols in the midst of the Covid-19 pandemic.